The Inclusion of Learners with Moderate General Learning Disabilities and Challenging Behaviours in School and Class Activities in Special Schools. - Colum, Miriam (Irish Association of Teachers in Special Education (IATSE), 2020)
Challenging behaviours (CB) are common among learners with special educational needs and can impact on inclusive practices in educational settings. The current study highlights some factors that support staff in the inclusion of learners with Moderate General Learning Disabilities (ModGLD) and CB in school and during class activities. The research focus is on the perspectives of teachers and principals in six midland and west of Ireland special schools for learners with ModGLD. The research question is “What are the factors that facilitate the inclusion of pupils with ModGLD exhibiting CB in school and during class activities in special schools”. Findings suggest that while some barriers exist such as training, other factors such as school setting, leadership, teacher confidence and competence, collaboration and the support of Special Needs Assistants (SNA) serve to facilitate the inclusion of this cohort of learners.
Keywords: Inclusion; special schools; moderate general learning disability; challenging behaviours; barriers to inclusion; barriers; Inclusive education; Disability; Education; ModGLD; Special Needs Assistants; SNA; Special Educational Needs; Education--Ireland